Effects of Habitat Heterogeneity and Hunting on the Occupancy and Activity Pattern of Terrestrial Mammals in the Interior Parts of Sarawak - Cheok, Melynda Ka Yi (Universiti Malaysia Sarawak(UNIMAS), 2019)
Poaching and loss of habitat are two of the main problems faced by the wildlife of Borneo. Mammalian species respond differently to habitat alterations, with some communities more sensitive than others to environmental distresses over time. Medium to large-bodied mammals are often hunted for consumption and sale, and therefore this study focused on the effect of hunting on the occupancy and activity patterns of terrestrial mammals in interior Sarawak. Three types of approaches were used in conducting this research, which includes investigating the distribution and daily activity patterns of hunted animals via motion triggered infrared camera traps, describing the habitat heterogeneity of the sampling sites, and undertaking interview surveys on local communities who hunt these animals. A total of 103 of camera trap sites data were used due to malfunction of some camera traps, with deployment period from May 2014 until January 2015 in Pelagus, Kapit, and May 2015 until June 2016 in Ulu Baram, Miri and Ulu Baleh, Kapit. Species richness and species assemblages composition of wildlife community in the three study sites were relatively similar, although there were several mammalian species with obvious differences in activity pattern observed between sites. Occupancy analysis using R software assessed the types of habitat that were more likely to be inhibited according to each studied species, with types of forest, elevation, and frequency of vines is associated with the persistence of some mammals in this study. The dependency of local community on wildlife seems to also influence the occupancy and activity patterns of mammals. Overall, this study demonstrates the dynamics and threats to wildlife in relation to anthropogenic disturbance such as habitat deterioration and hunting. It is hoped that this information could provide baseline information to protect and manage wildlife of similar habitats in Borneo.